PERSEPSI PEGAWAI ASURANSI TERHADAP INDUSTRI PERASURANSIAN: STUDI KASUS DI TIGA KABUPATEN JAWA TIMUR - Ayu Retsi Lestari (Universitas Katolik Soegijapranata Semarang, 2016)
This study examines employees characteristic of insurance companies and try to assess employee perceptions and loyalties on their companies they are working. The objects of this study are employees of insurance in a number of companies in the district of Jember, Bodowoso, and Lumajang. Respondents were selected randomly without regard to their job positions. Cross tabulation analysis are used to determine the demographic portrait of the employees. Analysis of the 70 respondents indicated the following conclusions. First, the distribution of insurance employees in the three districts studied was dominated by productive age and the majority of employees are male. They feel comfortable working in the insurance industry and is ready to work with high loyalty. Second, insurance employees have a high loyalty to keep working at the company due to the belief that their future is assured. Such loyalty is supported by the ability of employees to maintain the good name of the company and the belief that company's success is the success of employees too.